Pengarusutamaan Moderasi Beragama Bagi Pemuda Desa Sikayu Melalui Pendekatan ABCD (Asset Based Community Development) - Fatimah, Siti; Adib, Shohibul; Muzayyin, Muzayyin; Chamidi, Agus Salim; Triana Rahayu, Sesi; Fajar, Ali; Khusnia, Erikatul; Ma’wiyah, Lina Ni’matul; Aini, Lailatul Khurul; Arwani, Aziz; Cahyani, Arsela Titin (BALE LITERASI, 2023)
This service aims to strengthen religious moderation for youth in the Religious Moderation Village, Sikayu Village, Buayan District, Kebumen Regency. This activity was carried out during the Kebumen IAINU KKN program, namely July-August 2023. Actualization of activities to strengthen religious moderation through focus group discussion activities to dissect pocket books on strengthening religious moderation for youth in Sikayu Village. The approach used is ABCD (Asset Based Community Development). The data collection techniques used are interviews and questionnaires. The results of the implementation of this activity prove that the reinforcement that has been carried out has succeeded very well in the context of understanding youth about religious moderation and the importance of religious moderation. This will form the commitment of the youth in the Religious Moderation Village to spread the values of religious moderation.